Grenzbearbeitungen – methodologische Überlegungen zu einer sozialwissenschaftlichen Forschungsperspektive - Haker, Christoph; Otterspeer, Lukas (Grenzen auflösen – Grenzen ziehen: Grenzbearbeitungen zwischen Erziehungswissenschaft, Politik und Gesellschaft)

Antiakademismus heute - Haker, Christoph; Otterspeer, Lukas; Schildknecht, Lukas (Demokratie unter Druck)

Von der Axiomatik bis zur Schnittstellenaufgabe: Entwicklung und Erforschung eines ganzheitlichen Lehrkonzepts für eine Veranstaltung Geometrie für Lehramtsstudierende - Hoffmann, Max
Vorgestellt wird ein Entwicklungsforschungsprojekt zur Konzeption und Durchführung einer Veranstaltung "Geometrie für Lehramtsstudierende". Die Schwerpunkte des Projekts sind zum einen die inhaltliche Gestaltung der Veranstaltung und zum anderen die Umsetzung von Professionsorientierung. Bezogen auf den inhaltlichen Aufbau wird das auf metrischen Räumen aufbauende Axiomensystem der "Saccheri-Ebene" vorgestellt und mit alternativen axiomatischen Zugängen zur ebenen Geometrie verglichen. Die Frage nach der Umsetzung von Professionsorientierung in Fachveranstaltungen ist eng mit der Problematik der zweiten Diskontinuität verbunden. In der Arbeit wird dieses Problem auf Grundlage der Synthese von theoretischen Hintergründen zur Bedeutung von mathematischem Wissen und Können für professionelle Handlungskompetenz von Mathematiklehrkräften diskutiert und darauf aufbauend werden theoriebasierte Entwurfsprinzipien für professionsorientierte Fachveranstaltungen entworfen. Zentrale Elemente der methodischen Gestaltung sind die sogenannten "Schnittstellenwochen" zu den Themen Kongruenz und Symmetrie sowie das begleitende Schnittstellen-ePortfolio. Das zentrale Ergebnis der Arbeit ist ein theoretisch fundiertes und empirisch evaluiertes ganzheitliches Veranstaltungskonzept für eine professionsorientierte Geometrie-Veranstaltung für Lehramtsstudierende, dessen Konzeption auf andere Fachveranstaltungen übertragbar ist. Darüber hinaus ergeben sich im Rahmen der durchgeführten Entwicklungsforschung verschiedene neue Beiträge zur Geometriedidaktik in Schule- und Hochschule.

Alles wird gut, immer (Rezension) - Lammer, Christina (KinderundJugendmedien.de)

Schützenfeste@home und "gesicherte Brauchtumszonen". Eine ‚Geschichte in Echtzeit‘ von Ritualen, Bräuchen und Festen in der Coronakrise - Leineweber, Jonas (Westfalen/Lippe - historisch)

INVESTIGATION OF THE PROCESS PARAMETERS AND GEOMETRY DEPENDENT SHRINKAGE BEHAVIOR OF RASTER LINES IN THE FUSED DEPOSITION MODELING PROCESS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Rezension zu: Fickers, Andreas/Griset, Pascal: Communicating Europe. Technologies, Information, Events, Basingstoke, Hampshire 2019 - Schmitt, Martin (Francia-Recensio)

Ein Blick auf: Gestaltung des Übergangs in die Kindertageseinrichtung im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Meusel, Sarah; Heberle, Kathrin

wiḥdat ad-Dīn (Einheit der Religionen) - Abdelrahem, Mohammed (At-Taʿāyuš wa-t-taʿāruf fī l-islām – mafāhīm muyassara (Zusammenleben und Kennenlernen im Islam - Einführungsbegriffe))
Keywords: Dialog der Religionen; interreligiöser Dialog; Komparative Theologie; Islam und Christentum

Transitivitätscharakteristika als Werkzeug in der systematischen qualitativen Metaphernanalyse - Karsten, Andrea; Schwede, Jana; Körber, Miriam; Scharlau, Ingrid (Die Praxis der systematischen Metaphernanalyse: Anwendungen und Anschlüsse)

Schöpfung, Universität und Schule - Breckner, Anne

Wissenstransfer. Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung
Der Terminus Wissenstransfer hat in den letzten Jahren verstärkt an Bedeutung gewonnen. Er bezieht sich auf die Zirkulation von Wissen zwischen Systemen, Organisationen oder Parteien, etwa zwischen Hochschulen und Gesellschaft. Damit ist nicht ‚nur‘ der Transfer wissenschaftlicher Erkenntnisse in gesellschaftliche Kontexte gemeint, sondern vielmehr - über den Erwerb und die Weitergabe von Wissen hinaus - der Dialog und die Diskursbildung zwischen Wissenschaft und Gesellschaft. Der vorliegende Band nimmt dabei entstehende Aufgaben, Herausforderungen und Chancen kulturwissenschaftlicher Forschung in den Blick. Entgegen der Annahme, Projekte aus dem Feld der Kulturwissenschaften würden im Bereich des Abstrakten verbleiben, präsentiert er Beispiele kulturwissenschaftlicher Forschung, die Theorie und Praxis berücksichtigen sowie die Verzahnung von theoretischen Erkenntnissen und ihr Mitwirken an gesellschaftlichen Diskursen verdeutlichen.

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Wissenschaftsdidaktik als Verständigung über wissenschaftliches Handeln – eine Auslegeordnung - Jenert, Tobias; Scharlau, Ingrid (Wissenschaftsdidaktik I: Einführung)
Im Zentrum Beitrags steht die Frage nach dem Spezifischen einer Didaktik im Wissenschafts- bzw. Hochschulkontext. Dabei hat die Organisation des Wissenschaftssystems in Disziplinen bzw. disziplinäre Gemeinschaften eine besondere Bedeutung. Disziplinen entwickeln spezifische Praktiken, die das Handeln ihrer Angehörigen prägen und sich in Fachkulturen zeigen. Diese Praktiken werden insbesondere an kommunikativen Artefakten sichtbar. Für Personen außerhalb einer disziplinären Gemeinschaft und ganz besonders für jene, die keinen direkten Bezug zum Wissenschaftssystem haben, sind disziplinäre Praktiken häufig schwer zu erschließen. Unsere Konzeption von Wissenschaftsdidaktik lenkt den Blick auf die impliziten Praktiken wissenschaftlicher Disziplinen. Aufgabe von Wissenschaftsdidaktik ist es dem- nach, erstens die impliziten disziplinären Sinnstrukturen, die hinter bestimmten Prak- tiken stehen und in kommunikativen Handlungen und Artefakten verschlüsselt sind, zu entschlüsseln. Zweitens ist es notwendig, die Wahrnehmung disziplinärer Praktiken durch die Studierenden zu analysieren und Differenzen zum Sinnverstehen von Wissenschaftler:innen zu identifizieren. Ausgehend davon kann dann drittens auf eine Verständigung über die Praktiken und deren Sinngehalt hingearbeitet werden. Der Beitrag formuliert die Grundzüge einer Wissenschaftsdidaktik, welche Verständigung über die Praktiken wissenschaftlicher Disziplinen zu einem Kernbestandteil akademischer Lehre macht. Dazu gehört auch ein Moment von Wissenschaftskritik, das auf die Disziplinen und deren Praktiken selbst zurückwirkt. Wissenschaftsdidaktik in diesem Sinne verlangt, den Blick Dritter auf die Praktiken der eigenen Disziplin einzunehmen. Dazu gehör auch, sich einzugestehen, wenn Praktiken keinen Sinn für wissenschaftliche Erkenntnisprozesse (mehr) aufweisen bzw. diesen verloren haben.
Keywords: Wissenschaftsdidaktik; Fachsozialisation; Wissenschaftskritik; Verständigung; Fachkultur; akademische Praktiken; Unterrichtsfach Psychologie

Wissenschaftskommunikation als Verständigung: Chance für die Hochschulentwicklung?! - Jenert, Tobias; Scharlau, Ingrid (Zeitschrift für Hochschulentwicklung)

A density-functional theory study of hole and defect-bound exciton polarons in lithium niobate - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (Crystals)
Hole polarons and defect-bound exciton polarons in lithium niobate are investigated by means of density-functional theory, where the localization of the holes is achieved by applying the +U approach to the oxygen 2p orbitals. We find three principal configurations of hole polarons: (i) self-trapped holes localized at displaced regular oxygen atoms and (ii) two other configurations bound to a lithium vacancy either at a threefold coordinated oxygen atom above or at a two-fold coordinated oxygen atom below the defect. The latter is the most stable and is in excellent quantitative agreement with measured g factors from electron paramagnetic resonance. Due to the absence of mid-gap states, none of these hole polarons can explain the broad optical absorption centered between 2.5 and 2.8 eV that is observed in transient absorption spectroscopy, but such states appear if a free electron polaron is trapped at the same lithium vacancy as the bound hole polaron, resulting in an exciton polaron. The dielectric function calculated by solving the Bethe–Salpeter equation indeed yields an optical peak at 2.6 eV in agreement with the two-photon experiments. The coexistence of hole and exciton polarons, which are simultaneously created in optical excitations, thus satisfactorily explains the reported experimental data.

„Behinderung“ als Thema von Unterricht. Eine rekonstruktive Fallstudie zur (De-)Konstruktion von Dis*ability - Büttner, Denise; Frank, Magnus; Geier, Thomas (Lehren und Lernen in Differenzverhältnissen)

Learning Concept Lengths Accelerates Concept Learning in ALC - KOUAGOU, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (The Semantic Web)

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung (An Empirical Analysis of Firms’ Hidden Cost of Taxation) - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren
Keywords: General Earth and Planetary Sciences; General Environmental Science

Towards an Amended Arm's Length Principle - Tackling complexity and implementing destination rules in transfer pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren

Firms' Tax Rate Misperception: Measurement, Drivers, and Distortionary Effects - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Sureth-Sloane, Caren

Mathematik-Vorkurse zur Vorbereitung auf das Studium – Zielsetzungen und didaktische Konzepte - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Mini-Aufgaben in mathematischen Übungsgruppen zur Analysis: Charakteristika von Aufgaben und Abstimmungsverhalten von Studierenden - Bauer, Thomas; Biehler, Rolf; Lankeit, Elisa (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Ein Rahmenmodell für hochschuldidaktische Maßnahmen in der Mathematik - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Acquiring religious words: Dialogical and individual construction of the word’s meaning - Viertel, Franziska; Reis, Oliver; Rohlfing, Katharina (Philosophical Transactions of the Royal Society B)

Artefakte als (An-)Zeiger der Zeit. Praxistheoretische Analysen zu religiösen Artefakten an einer Katholischen Schule - Hoyer, Isabelle; Reis, Oliver

Lernstandserhebung/-diagnostik, wissenschaftstheoretisch - Reis, Oliver (WiReLex 2/2022)

Evaluation von Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Schürmann, Mirko; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

PATTERNS 2022 The Fourteenth International Conferences on Pervasive Patterns and Applications

Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies)
Transformations of various kinds have always shaped societies and especially its cultures and research – triggered, for example, by wars, revolutions, shifts in social orders, pandemics, etc. They have led to uncertainty and social upheaval, but also to innovation and change. As pop music cultures, in their entire breadth, can be described as seismographs of social, political, economic, ecological, media, artistic, and technological transformations, in and through them, fields of tensions, disruptions, and lines of conflict become not only visible, audible, and perceptible, but also communicable and thus, negotiable. Volume No. 2 of ~Vibes – The IASPM D-A-CH Series, which is based on the 4th Biennial IASPM D-A-CH conference at Paderborn University/online, takes a closer look at the transformative moments of pop music cultures by theorizing, empiricizing, historicizing, and, finally, politicizing them.

Contradict – Ideas for a New World. A Talk between Thomas Burkhalter and Manuel Troike about the documentary film Contradict. - Burkhalter, Thomas; Troike, Manuel (Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies))
Manuel Troike talks to the Swiss ethnomusicologist Dr. Thomas Burkhalter about his music documentary Contradict – Ideas for a New World. Together with Peter Guyer, Burkhalter gives six musicians from Ghana a chance to speak, to look at the changing values of our time from the African continent, and to show how trends, ideas and visions are increasingly decentralised in a globalised world.

Inklusion, Exklusion, Usurpation. Strategien der Übernahme diskursiver Widerstands- und Protest- Positionen im 'Dritten Reich' sowie in der DDR anhand des rechtspopulistischen Blogs Politically Incorrect - Markewitz, Friedrich (Akten des XIV. Internationalen Germanistenkongresses Palermo 2021: Wege der Germanistik in transkultureller Perspektive)

Tarnschriften als Medium des diskursiven Bedeutungsbruchs sowie der diskursiven Bedeutungserweiterung und -destabilisierung - Markewitz, Friedrich (Zeitschrift für Literaturwissenschaft und Linguistik)
Trotz zunehmender Reglementierungen des Sprachraums im ›Dritten Reich‹ findet sich eine Vielzahl opponierender, resistierender und widerständischer Sprachhandlungen. Eine wichtige Strategie im durch das Aufeinanderprallen inkommensurabler Diskursarten entstehenden semantischen Kampf um Deutungsmuster ist die der Potenzierung möglicher Bedeutungszusammenhänge durch Veruneindeutigungen, Verschleierungen und andere Formen indirekter Kommunikation, um so widerständische Botschaften in den NS-Diskurs versuchsweise einschleusen zu können. Oft auf den Ebenen der Lexik oder der Äußerung untersucht, will dieser Aufsatz einen texttypologischen Beitrag zur Erschließung von Veruneindeutigungspotenzialen im ›Dritten Reich‹ leisten. Anhand der im linguistischen Forschungsdiskurs bisher nicht wahrgenommenen textuellen Gattung Tarnschrift sollen anhand ihrer spezifischen Charakteristika Möglichkeiten des Bedeutungsbruchs sowie der Bedeutungserweiterung und -destabilisierung reflektiert werden, um so dem bestehenden Forschungsdesiderat der Aufarbeitung widerständischer Kommunikationsstrategien wie textueller Zeugnisse zu begegnen.

Einleitung - Markewitz, Friedrich; Dang-Anh, Mark; Kämper, Heidrun; Scholl, Stefan; Schuster, Britt-Marie; Wilk, Nicole M. (Im Nationalsozialismus. Praktiken – Kommunikation – Diskurse. Teil 1)

Wahr-Sagen im Widerstand - Markewitz, Friedrich (Im Nationalsozialismus. Praktiken – Kommunikation – Diskurse. Teil 1)

Freiheit - Markewitz, Friedrich; Wilk, Nicole M. (Im Nationalsozialismus. Praktiken – Kommunikation – Diskurse. Teil 2)

Tagebuch - Markewitz, Friedrich; Kämper, Heidrun (Im Nationalsozialismus. Praktiken – Kommunikation – Diskurse. Teil 2)

Rede - Markewitz, Friedrich; Kämper, Heidrun (Im Nationalsozialismus. Praktiken – Kommunikation – Diskurse. Teil 2)

Guidelines zur Annotation von Widerstandspraktiken in CATMA 5.0 im Rahmen des DFG-Projektes "Heterogene Widerstandskulturen. Sprachliche Praktiken des Sich-Widersetzens von 1933 bis 1945" - Markewitz, Friedrich; Schuster, Britt-Marie; Wilk, Nicole M.

Stimulation and Enhancement of Near‐Band‐Edge Emission in Zinc Oxide by Distributed Bragg Reflectors - Kothe, Linda; Albert, Maximilian; Meier, Cedrik; Wagner, Thorsten; Tiemann, Michael (Advanced Materials Interfaces)
The free exciton transition (near-band-edge emission, NBE) of ZnO at ≈388 nm can be strongly enhanced and even stimulated by an underlying photonic structure. 1D Photonic crystals, so-called distributed Bragg reflectors, are utilized to suppress the deep-level emission of ZnO (DLE, ≈500–530 nm). The reflector stacks are fabricated in a layer-by-layer procedure by wet-chemical synthesis. They consist of low-ε porous SiO2 layers and high-ε TiO2 layers. Varying the thickness of the SiO2 layers allows tuning the optical bandgap in a wide range between ≈420 and 800 nm. A ZnO layer is deposited on top of the reflector stacks by sol–gel synthesis. The spontaneous photoluminescence (PL) emission of the ZnO film is modulated by the photonic structure. When the optical bandgap of the reflector is in resonance with the deep-level emission of ZnO (DLE, ≈500–530 nm), then this defect-related emission mode is suppressed. Strong NBE emission is observed even when the ZnO layer does not show any NBE emission (due to low crystallinity) in the absence of the photonic structure. With this cost-efficient synthesis method, emitters for, e.g., luminescent gas sensors can be fabricated.
Keywords: Mechanical Engineering; Mechanics of Materials

User Involvement in Training Smart Home Agents - Sieger, Leonie Nora; Hermann, Julia; Schomäcker, Astrid; Heindorf, Stefan; Meske, Christian; Hey, Celine-Chiara; Doğangün, Ayşegül (International Conference on Human-Agent Interaction)
Smart home systems contain plenty of features that enhance wellbeing in everyday life through artificial intelligence (AI). However, many users feel insecure because they do not understand the AI’s functionality and do not feel they are in control of it. Combining technical, psychological and philosophical views on AI, we rethink smart homes as interactive systems where users can partake in an intelligent agent’s learning. Parallel to the goals of explainable AI (XAI), we explored the possibility of user involvement in supervised learning of the smart home to have a first approach to improve acceptance, support subjective understanding and increase perceived control. In this work, we conducted two studies: In an online pre-study, we asked participants about their attitude towards teaching AI via a questionnaire. In the main study, we performed a Wizard of Oz laboratory experiment with human participants, where participants spent time in a prototypical smart home and taught activity recognition to the intelligent agent through supervised learning based on the user’s behaviour. We found that involvement in the AI’s learning phase enhanced the users’ feeling of control, perceived understanding and perceived usefulness of AI in general. The participants reported positive attitudes towards training a smart home AI and found the process understandable and controllable. We suggest that involving the user in the learning phase could lead to better personalisation and increased understanding and control by users of intelligent agents for smart home automation.
Keywords: human-agent interaction; smart homes; supervised learning; participation

EvoLearner: Learning Description Logics with Evolutionary Algorithms - Heindorf, Stefan; Blübaum, Lukas; Düsterhus, Nick; Werner, Till; Golani, Varun Nandkumar; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (WWW)
Classifying nodes in knowledge graphs is an important task, e.g., predicting missing types of entities, predicting which molecules cause cancer, or predicting which drugs are promising treatment candidates. While black-box models often achieve high predictive performance, they are only post-hoc and locally explainable and do not allow the learned model to be easily enriched with domain knowledge. Towards this end, learning description logic concepts from positive and negative examples has been proposed. However, learning such concepts often takes a long time and state-of-the-art approaches provide limited support for literal data values, although they are crucial for many applications. In this paper, we propose EvoLearner - an evolutionary approach to learn ALCQ(D), which is the attributive language with complement (ALC) paired with qualified cardinality restrictions (Q) and data properties (D). We contribute a novel initialization method for the initial population: starting from positive examples (nodes in the knowledge graph), we perform biased random walks and translate them to description logic concepts. Moreover, we improve support for data properties by maximizing information gain when deciding where to split the data. We show that our approach significantly outperforms the state of the art on the benchmarking framework SML-Bench for structured machine learning. Our ablation study confirms that this is due to our novel initialization method and support for data properties.

CovidPubGraph: A FAIR Knowledge Graph of COVID-19 Publications - Pestryakova, Svetlana; Vollmers, Daniel; Sherif, Mohamed; Heindorf, Stefan; Saleem, Muhammad; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Scientific Data)

Laborpraktika auf Distanz. Ansätze in den Naturwissenschaften - Bauer, Anna; Sacher, Marc; Habig, Sebastian; Fechner, Sabine (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)

Resistivity and Formation of Intermetallic Layer in Aluminum-Steel Clad Strip - Křivská, B; Šlapáková, M; Králík, R; Bajtošová, L; Cieslar, M; Grydin, Olexandr; Stolbchenko, M; Schaper, Mirko (IOP Conference Series: Materials Science and Engineering)

Influence of Plasmon Resonances and Symmetry Effects on Second Harmonic Generation in WS2–Plasmonic Hybrid Metasurfaces - Spreyer, Florian; Ruppert, Claudia; Georgi, Philip; Zentgraf, Thomas (ACS Nano)
The nonlinear process of second harmonic generation (SHG) in monolayer (1L) transition metal dichalcogenides (TMD), like WS2, strongly depends on the polarization state of the excitation light. By combination of plasmonic nanostructures with 1L-WS2 by transferring it onto a plasmonic nanoantenna array, a hybrid metasurface is realized impacting the polarization dependency of its SHG. Here, we investigate how plasmonic dipole resonances affect the process of SHG in plasmonic–TMD hybrid metasurfaces by nonlinear spectroscopy. We show that the polarization dependency is affected by the lattice structure of plasmonic nanoantenna arrays as well as by the relative orientation between the 1L-WS2 and the individual plasmonic nanoantennas. In addition, such hybrid metasurfaces show SHG in polarization states, where SHG is usually forbidden for either 1L-WS2 or plasmonic nanoantennas. By comparing the SHG in these channels with the SHG generated by the hybrid metasurface components, we detect an enhancement of the SHG signal by a factor of more than 40. Meanwhile, an attenuation of the SHG signal in usually allowed polarization states is observed. Our study provides valuable insight into hybrid systems where symmetries strongly affect the SHG and enable tailored SHG in 1L-WS2 for future applications.

Extending Business Model Development Tools with Consolidated Expert Knowledge - Gottschalk, Sebastian; Kirchhoff, Jonas; Engels, Gregor (Business Modeling and Software Design)

The Strong Scaling Advantage of FPGAs in HPC for N-body Simulations - Menzel, Johannes; Plessl, Christian; Kenter, Tobias (ACM Transactions on Reconfigurable Technology and Systems)
N-body methods are one of the essential algorithmic building blocks of high-performance and parallel computing. Previous research has shown promising performance for implementing n-body simulations with pairwise force calculations on FPGAs. However, to avoid challenges with accumulation and memory access patterns, the presented designs calculate each pair of forces twice, along with both force sums of the involved particles. Also, they require large problem instances with hundreds of thousands of particles to reach their respective peak performance, limiting the applicability for strong scaling scenarios. This work addresses both issues by presenting a novel FPGA design that uses each calculated force twice and overlaps data transfers and computations in a way that allows to reach peak performance even for small problem instances, outperforming previous single precision results even in double precision, and scaling linearly over multiple interconnected FPGAs. For a comparison across architectures, we provide an equally optimized CPU reference, which for large problems actually achieves higher peak performance per device, however, given the strong scaling advantages of the FPGA design, in parallel setups with few thousand particles per device, the FPGA platform achieves highest performance and power efficiency.

Forming Simulation of Tailored Press Hardened Parts - Triebus, Marcel; Reitz, Alexander; Grydin, Olexandr; Grenz, Julian; Schneidt, Andreas; Erhardt, Rüdiger; Tröster, Thomas; Schaper, Mirko (13th European LS-DYNA Conference 2021)

Fiber response to pin penetration in dry woven fabric using numerical analysis - Droß, M.; Heyser, Per; Meschut, Gerson; Hürkamp, A.; Dröder, K. (Journal of Advanced Joining Processes)

Aus der Forschung in die Anwendung - Materialqualifizierung im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffland NRW report)

Validation of an Online State Estimation Concept for Microscopic Traffic Simulations◆ - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (2021 IEEE Transportation Electrification Conference & Expo (ITEC))
This paper deals with a novel method for the online fitting of a microscopic traffic simulation model to the current state of a real world traffic area. The traffic state estimation is based on limited data of different measurement sources and guarantees general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. The research is embedded in the challenge of improving the traffic by controlling the traffic light systems (TLS) of the examined area. Therefore, the current traffic state and the predicted route choices of individual road users are the matter of interest. The concept is generally transferable to any road traffic system. To give an impression of the accuracy and potential of the approach, the validation and first application results are presented.

Transitioning to Condition-Based Maintenance on the Distribution Grid: Deriving Design Principles from a Qualitative Study - zur Heiden, Philipp; Priefer, Jennifer (Pre-Conference 16th International Congress on Wirtschaftsinformatik at Universität Duisburg-Essen)

Ansätze zur Diagnose und Förderung von Problemlösefähigkeiten in der Studieneingangsphase Physik - Lahme, Simon; Bauer, Anna; Reinhold, Peter (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Erweiterung des epistemologischen Verständnisses durch Konfrontation mit anomalen Daten. - Pollmeier, Pascal; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

Guaranteeing Properties of Reconfigurable Hardware Circuits with Proof-Carrying Hardware - Wiersema, Tobias
Previous research in proof-carrying hardware has established the feasibility and utility of the approach, and provided a concrete solution for employing it for the certification of functional equivalence checking against a specification, but fell short in connecting it to state-of-the-art formal verification insights, methods and tools. Due to the immense complexity of modern circuits, and verification challenges such as the state explosion problem for sequential circuits, this restriction of readily-available verification solutions severely limited the applicability of the approach in wider contexts. This thesis closes the gap between the PCH approach and current advances in formal hardware verification, provides methods and tools to express and certify a wide range of circuit properties, both functional and non-functional, and presents for the first time prototypes in which circuits that are implemented on actual reconfigurable hardware are verified with PCH methods. Using these results, designers can now apply PCH to establish trust in more complex circuits, by using more diverse properties which they can express using modern, efficient property specification techniques.
Keywords: Proof-Carrying Hardware; Formal Verification; Sequential Circuits; Non-Functional Properties; Functional Properties

Examination of hazardous situations in industrial closed-loop processes using dynamic simulations - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny (Chemical Engineering Transactions)

Option Implied Tax Rate Expectations - Eberbach, Jelena; Sureth-Sloane, Caren; Uhrig-Homburg, Marliese

TaintBench: Automatic real-world malware benchmarking of Android taint analyses - Luo, Linghui; Pauck, Felix; Piskachev, Goran; Benz, Manuel; Pashchenko, Ivan; Mory, Martin; Bodden, Eric; Hermann, Ben; Massacci, Fabio (Empirical Software Engineering)
Due to the lack of established real-world benchmark suites for static taint analyses of Android applications, evaluations of these analyses are often restricted and hard to compare. Even in evaluations that do use real-world apps, details about the ground truth in those apps are rarely documented, which makes it difficult to compare and reproduce the results. To push Android taint analysis research forward, this paper thus recommends criteria for constructing real-world benchmark suites for this specific domain, and presents TaintBench, the first real-world malware benchmark suite with documented taint flows. TaintBench benchmark apps include taint flows with complex structures, and addresses static challenges that are commonly agreed on by the community. Together with the TaintBench suite, we introduce the TaintBench framework, whose goal is to simplify real-world benchmarking of Android taint analyses. First, a usability test shows that the framework improves experts’ performance and perceived usability when documenting and inspecting taint flows. Second, experiments using TaintBench reveal new insights for the taint analysis tools Amandroid and FlowDroid: (i) They are less effective on real-world malware apps than on synthetic benchmark apps. (ii) Predefined lists of sources and sinks heavily impact the tools’ accuracy. (iii) Surprisingly, up-to-date versions of both tools are less accurate than their predecessors.

К ОПРЕДЕЛЕНИЮ ПРОЧНОСТИ КЛЕЕВОГО СОЕДИНЕНИЯ В МНОГОСЛОЙНЫХ МАТЕРИАЛАХ ПУТЕМ ИССЛЕДОВАНИЯ ОБЛАСТЕЙ РАСТАЛКИВАНИЯ БЕГУЩИХ УПРУГИХ ВОЛН - Lugovtsova, Yevgeniya; Zeipert, Henning; Johannesmann, Sarah; Nicolai, Marcel; Prager, Jens; Henning, Bernd (МАТЕМАТИЧЕСКОЕ МОДЕЛИРОВАНИЕ В ЕСТЕСТВЕННЫХ НАУКАХ - XXX Всероссийская школа-конференция)

Entwicklung von Praxiskompetenz durch Kooperationsprozesse von Lehrkräften - Bloh, Thiemo (Zeitschrift für Bildungsforschung)
Zusammenfassung Lehrkräftekooperation wird generell eine positive Bedeutung in Bezug auf Schul- und Unterrichtsentwicklung zugeschrieben. Dabei sind empirische Belege für eine positive Wirksamkeit nach wie vor kaum vorhanden, es gibt sogar Befunde zu ‚negativen‘ Konsequenzen von Lehrkräftekooperation. Um diese Widersprüchlichkeit zu klären, wurde in der vorliegenden Arbeit Kooperation nicht als Instrument bzw. als Technik betrachtet, sondern als soziale Praxis verstanden, in der eigenlogisches, kollektiv-implizites Wissen (re)produziert wird (Community of Practice). Parallel dazu wurde ein praxeologisches Kompetenzverständnis (Praxiskompetenz) eingeführt, das wesentlich auf die Praxeologie Pierre Bourdieus zurückgeht und den Zusammenhang zwischen Lehrkräftekooperation als Community of Practice und kollektiv strukturierter, individueller Kompetenz theoretisch verdeutlicht. Die empirischen Befunde, welche mittels der Dokumentarischen Methode generiert wurden, verweisen auf die Bedeutung unterschiedlicher Relationslogiken (Nicht-Passung, Entfaltung, Herausforderung) für das ‚Lernen‘ von oder innerhalb von Praxiskompetenz(en) und damit auch auf die Wichtigkeit einer grundlegend kollektiv gerahmten Perspektive auf Lehrkräftekooperation. Vor diesem Hintergrund ist ein allzu positiver Blick auf Lehrkräftekooperationsprozesse kritisch zu betrachten.

Far-Field Automatic Speech Recognition - Haeb-Umbach, Reinhold; Heymann, Jahn; Drude, Lukas; Watanabe, Shinji; Delcroix, Marc; Nakatani, Tomohiro (Proceedings of the IEEE)
The machine recognition of speech spoken at a distance from the microphones, known as far-field automatic speech recognition (ASR), has received a significant increase of attention in science and industry, which caused or was caused by an equally significant improvement in recognition accuracy. Meanwhile it has entered the consumer market with digital home assistants with a spoken language interface being its most prominent application. Speech recorded at a distance is affected by various acoustic distortions and, consequently, quite different processing pipelines have emerged compared to ASR for close-talk speech. A signal enhancement front-end for dereverberation, source separation and acoustic beamforming is employed to clean up the speech, and the back-end ASR engine is robustified by multi-condition training and adaptation. We will also describe the so-called end-to-end approach to ASR, which is a new promising architecture that has recently been extended to the far-field scenario. This tutorial article gives an account of the algorithms used to enable accurate speech recognition from a distance, and it will be seen that, although deep learning has a significant share in the technological breakthroughs, a clever combination with traditional signal processing can lead to surprisingly effective solutions.

A Comparison of Multi-View Learning Strategies for Satellite Image-based Real Estate Appraisal - Kucklick, Jan-Peter; Müller, Oliver (The AAAI-21 Workshop on Knowledge Discovery from Unstructured Data in Financial Services)

Derivative-Free Multiobjective Trust Region Descent Method Using Radial Basis Function Surrogate Models - Berkemeier, Manuel Bastian; Peitz, Sebastian (Mathematical and Computational Applications)
We present a flexible trust region descend algorithm for unconstrained and convexly constrained multiobjective optimization problems. It is targeted at heterogeneous and expensive problems, i.e., problems that have at least one objective function that is computationally expensive. The method is derivative-free in the sense that neither need derivative information be available for the expensive objectives nor are gradients approximated using repeated function evaluations as is the case in finite-difference methods. Instead, a multiobjective trust region approach is used that works similarly to its well-known scalar pendants. Local surrogate models constructed from evaluation data of the true objective functions are employed to compute possible descent directions. In contrast to existing multiobjective trust region algorithms, these surrogates are not polynomial but carefully constructed radial basis function networks. This has the important advantage that the number of data points scales linearly with the parameter space dimension. The local models qualify as fully linear and the corresponding general scalar framework is adapted for problems with multiple objectives. Convergence to Pareto critical points is proven and numerical examples illustrate our findings.

Nonlinear Bicolor Holography Using Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Cinchetti, Mirko; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)

Distributed Online Service Coordination Using Deep Reinforcement Learning - Schneider, Stefan Balthasar; Qarawlus, Haydar; Karl, Holger (IEEE International Conference on Distributed Computing Systems (ICDCS))
Services often consist of multiple chained components such as microservices in a service mesh, or machine learning functions in a pipeline. Providing these services requires online coordination including scaling the service, placing instance of all components in the network, scheduling traffic to these instances, and routing traffic through the network. Optimized service coordination is still a hard problem due to many influencing factors such as rapidly arriving user demands and limited node and link capacity. Existing approaches to solve the problem are often built on rigid models and assumptions, tailored to specific scenarios. If the scenario changes and the assumptions no longer hold, they easily break and require manual adjustments by experts. Novel self-learning approaches using deep reinforcement learning (DRL) are promising but still have limitations as they only address simplified versions of the problem and are typically centralized and thus do not scale to practical large-scale networks. To address these issues, we propose a distributed self-learning service coordination approach using DRL. After centralized training, we deploy a distributed DRL agent at each node in the network, making fast coordination decisions locally in parallel with the other nodes. Each agent only observes its direct neighbors and does not need global knowledge. Hence, our approach scales independently from the size of the network. In our extensive evaluation using real-world network topologies and traffic traces, we show that our proposed approach outperforms a state-of-the-art conventional heuristic as well as a centralized DRL approach (60% higher throughput on average) while requiring less time per online decision (1 ms).
Keywords: network management; service management; coordination; reinforcement learning; distributed

Von datenbasierter zu datengetriebener Geschäftsmodellentwicklung: Ein Überblick über Software-Tools und deren Datennutzung - Gottschalk, Sebastian; Yigitbas, Enes
Die kontinuierliche Weiterentwicklung des eigenen Geschäftsmodells ist für eine Organisation von entscheidender Bedeutung, um wettbewerbsfähig und somit nachhaltig erfolgreich zu bleiben. Während für die Entwicklung neuer Geschäftsmodelle häufig Workshops und einfache Software-Tools zur Visualisierung genutzt werden, wurden in der Forschung bereits erste Ansätze von datengetriebener Geschäftsmodellentwicklung (GME) vorgestellt. Diese Ansätze nutzen dabei Daten, Informationen oder auch Wissen aus internen und externen Unternehmensquellen, um den GME-Prozess zu unterstützen. Innerhalb dieses Beitrags zeigen wir einige Ansätze aus der aktuellen Literatur und analysieren wie ihre Datennutzung den GME-Prozess unterstützt. Weiterhin stellen wir mit dem BMDL Feature Modeler ein Tool vor, welches den GME-Prozess mit Expertenwissen unterstützt.

Distributed merchandise management system - Göllner, Thomas; Schwarz, Jan-Hendrik; Gottschalk, Sebastian; Sauer, Stefan
The invention describes a distributed merchandise management system, in which the client, retailer and the manufacturer are linked by a network. This is implemented by a cloud storage (105), the cloud storage (105) comprising a means (105 a) for storing data, a means for receiving first data from a first network node (110), the first data being associated with a physical object, a means for receiving request data from a second network node (120), a means for receiving second data from a third network node (130), the second data being associated with the first data and comprising at least one data piece adapted to change the first data depending on the received request data, a means for changing the first data based at least in part on the second data and the request data, and a means for sending a changed portion of the first data from the cloud storage (105) to the first network node (110).

Optical secret sharing with cascaded metasurface holography - Georgi, Philip; Wei, Qunshuo; Sain, Basudeb; Schlickriede, Christian; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Science Advances)
Secret sharing is a well-established cryptographic primitive for storing highly sensitive information like encryption keys for encoded data. It describes the problem of splitting a secret into different shares, without revealing any information to its shareholders. Here, we demonstrate an all-optical solution for secret sharing based on metasurface holography. In our concept, metasurface holograms are used as spatially separable shares that carry encrypted messages in the form of holographic images. Two of these shares can be recombined by bringing them close together. Light passing through this stack of metasurfaces accumulates the phase shift of both holograms and optically reconstructs the secret with high fidelity. In addition, the hologram generated by each single metasurface can uniquely identify its shareholder. Furthermore, we demonstrate that the inherent translational alignment sensitivity between two stacked metasurface holograms can be used for spatial multiplexing, which can be further extended to realize optical rulers.

From Label Smoothing to Label Relaxation - Lienen, Julian; Hüllermeier, Eyke (Proceedings of the 35th AAAI Conference on Artificial Intelligence, AAAI)

Situation-specific Business Model Development Methods for Mobile App Developers - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Enterprise, Business-Process and Information Systems Modeling)
The development of effective business models is an essential task in highly competitive markets like mobile ecosystems. Existing development methods for these business models do not specifically focus that the development process profoundly depends on the situation (e.g., market size, regulations) of the mobile app developer. Here, a mismatch between method and situation can lead to poor resource management and longer development cycles. In software engineering, situational method engineering is used for software projects to configure a development method out of a method repository based on the project situation. Analogously, we support creating situation-specific business model development methods with a method base and new user roles. Here, the method engineer obtains the knowledge of the domain expert and stores it in the method base as elements, building blocks, and patterns. The expert knowledge is derived from a grey literature review on mobile development processes. After this, the method engineer constructs the development method based on the described situation of the business developer. We provide an open-source tool and evaluate it by constructing a local event platform's business model development method.
Keywords: Business Model Development; Situational Method Engineering; Mobile App; Business Model Development Tools

Application-Aware Intrusion Detection: A Systematic Literature Review, Implications for Automotive Systems, and Applicability of AutoML - Schubert, David; Eikerling, Hendrik; Holtmann, Jörg (Frontiers in Computer Science)
Modern and flexible application-level software platforms increase the attack surface of connected vehicles and thereby require automotive engineers to adopt additional security control techniques. These techniques encompass host-based intrusion detection systems (HIDSs) that detect suspicious activities in application contexts. Such application-aware HIDSs originate in information and communications technology systems and have a great potential to deal with the flexible nature of application-level software platforms. However, the elementary characteristics of known application-aware HIDS approaches and thereby the implications for their transfer to the automotive sector are unclear. In previous work, we presented a systematic literature review (SLR) covering the state of the art of application-aware HIDS approaches. We synthesized our findings by means of a fine-grained classification for each approach specified through a feature model and corresponding variant models. These models represent the approaches’ elementary characteristics. Furthermore, we summarized key findings and inferred implications for the transfer of application-aware HIDSs to the automotive sector. In this article, we extend the previous work by several aspects. We adjust the quality evaluation process within the SLR to be able to consider high quality conference publications, which results in an extended final pool of publications. For supporting HIDS developers on the task of configuring HIDS analysis techniques based on machine learning, we report on initial results on the applicability of AutoML. Furthermore, we present lessons learned regarding the application of the feature and variant model approach for SLRs. Finally, we more thoroughly describe the SLR study design.

What Is Unclear? Computational Assessment of Task Clarity in Crowdsourcing - Nouri, Zahra; Gadiraju, Ujwal; Engels, Gregor; Wachsmuth, Henning (Proceedings of the 32nd ACM Conference on Hypertext and Social Media)

Low Temperature Laser Sintering on a Standard System: First Attempts and Results with PA12 - Menge, Dennis; Schmid, Hans-Joachim
The laser sintering process has been a well-established AM process for many years. Disadvantages of LS are the low material variety and the thermal damage of the unprocessed material. The low temperature laser sintering attacks at this point and processes powder material at a build chamber temperature lower than the recrystallization temperature. This drastic reduction in temperature results in significantly less thermal damage to the material. This work deals with the low temperature laser sintering of Polyamide 12 (PA12) on a commercial, unmodified laser sintering system to compare it to standard laser sintered PA12 and to create the basis for low temperature laser sintering of high temperature materials on such a system. First results by changing the exposure parameters and by fixing parts on a building platform show a processing of PA12 on an EOS P396 at a build chamber temperature less than 100 °C instead of standard approx. 175 °C.
Keywords: Low Temp LS; Low Temperature Laser Sintering; Polyamid 12

Selective Etching of (111)B-Oriented AlxGa1−xAs-Layers for Epitaxial Lift-Off - Henksmeier, Tobias; Eppinger, Martin; Reineke, Bernhard; Zentgraf, Thomas; Meier, Cedrik; Reuter, Dirk (physica status solidi (a))
GaAs-(111)-nanostructures exhibiting second harmonic generation are new building blocks in nonlinear optics. Such structures can be fabricated through epitaxial lift-off using selective etching of Al-containing layers and subsequent transfer to glass substrates. Herein, the selective etching of (111)B-oriented AlxGa1−xAs sacrificial layers (10–50 nm thick) with different aluminum concentrations (x = 0.5–1.0) in 10% hydrofluoric acid is investigated and compared with standard (100)-oriented structures. The thinner the sacrificial layer and the lower the aluminum content, the lower the lateral etch rate. For both orientations, the lateral etch rates are in the same order of magnitude, but some quantitative differences exist. Furthermore, the epitaxial lift-off, the transfer, and the nanopatterning of thin (111)B-oriented GaAs membranes are demonstrated. Atomic force microscopy and high-resolution X-ray diffraction measurements reveal the high structural quality of the transferred GaAs-(111) films.
Keywords: epitaxial lift-off; GaAs/AlxGa1−xAs heterostructures; selective etching

Divide and Conquer: Hierarchical Network and Service Coordination - Schneider, Stefan Balthasar; Jürgens, Mirko; Karl, Holger (IFIP/IEEE International Symposium on Integrated Network Management (IM))
In practical, large-scale networks, services are requested by users across the globe, e.g., for video streaming. Services consist of multiple interconnected components such as microservices in a service mesh. Coordinating these services requires scaling them according to continuously changing user demand, deploying instances at the edge close to their users, and routing traffic efficiently between users and connected instances. Network and service coordination is commonly addressed through centralized approaches, where a single coordinator knows everything and coordinates the entire network globally. While such centralized approaches can reach global optima, they do not scale to large, realistic networks. In contrast, distributed approaches scale well, but sacrifice solution quality due to their limited scope of knowledge and coordination decisions. To this end, we propose a hierarchical coordination approach that combines the good solution quality of centralized approaches with the scalability of distributed approaches. In doing so, we divide the network into multiple hierarchical domains and optimize coordination in a top-down manner. We compare our hierarchical with a centralized approach in an extensive evaluation on a real-world network topology. Our results indicate that hierarchical coordination can find close-to-optimal solutions in a fraction of the runtime of centralized approaches.
Keywords: network management; service management; coordination; hierarchical; scalability; nfv

Situation-specific Development of Business Models for Services in Software Ecosystems - Gottschalk, Sebastian (Advanced Software Engineering. Doctorial Consortium)

Bias Silhouette Analysis: Towards Assessing the Quality of Bias Metrics for Word Embedding Models - Spliethöver, Maximilian; Wachsmuth, Henning (Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence, IJCAI-21)
Word embedding models reflect bias towards genders, ethnicities, and other social groups present in the underlying training data. Metrics such as ECT, RNSB, and WEAT quantify bias in these models based on predefined word lists representing social groups and bias-conveying concepts. How suitable these lists actually are to reveal bias - let alone the bias metrics in general - remains unclear, though. In this paper, we study how to assess the quality of bias metrics for word embedding models. In particular, we present a generic method, Bias Silhouette Analysis (BSA), that quantifies the accuracy and robustness of such a metric and of the word lists used. Given a biased and an unbiased reference embedding model, BSA applies the metric systematically for several subsets of the lists to the models. The variance and rate of convergence of the bias values of each model then entail the robustness of the word lists, whereas the distance between the models' values gives indications of the general accuracy of the metric with the word lists. We demonstrate the behavior of BSA on two standard embedding models for the three mentioned metrics with several word lists from existing research.

Generating Informative Conclusions for Argumentative Texts - Syed, Shahbaz; Al-Khatib, Khalid; Alshomary, Milad; Wachsmuth, Henning; Potthast, Martin (Proceedings of the Joint Conference of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Conference on Natural Language Processing (ACL-IJCNLP 2021): Findings)

Syntopical Graphs for Computational Argumentation Tasks - Barrow, Joe; Jain, Rajiv; Lipka, Nedim; Dernoncourt, Franck; Morariu, Vlad; Manjunatha, Varun; Oard, Douglas; Resnik, Philip; Wachsmuth, Henning (Proceedings of the Joint Conference of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Conference on Natural Language Processing (ACL-IJCNLP 2021))

Android App Analysis Benchmark Case Generation - Schott, Stefan

Nonlinear metasurface combining telecom-range intersubband transitions in GaN/AlN quantum wells with resonant plasmonic antenna arrays - Mundry, Jan; Spreyer, Florian; Jmerik, Valentin; Ivanov, Sergey; Zentgraf, Thomas; Betz, Markus (Optical Materials Express)
We realize and investigate a nonlinear metasurface taking advantage of intersubband transitions in ultranarrow GaN/AlN multi-quantum well heterostructures. Owing to huge band offsets, the structures offer resonant transitions in the telecom window around 1.55 µm. These heterostructures are functionalized with an array of plasmonic antennas featuring cross-polarized resonances at these near-infrared wavelengths and their second harmonic. This kind of nonlinear metasurface allows for substantial second-harmonic generation at normal incidence which is completely absent for an antenna array without the multi-quantum well structure underneath. While the second harmonic is originally radiated only into the plane of the quantum wells, a proper geometrical arrangement of the plasmonic elements permits the redirection of the second-harmonic light to free-space radiation, which is emitted perpendicular to the surface.

Credal Self-Supervised Learning - Lienen, Julian; Hüllermeier, Eyke (arXiv:2106.11853)
Self-training is an effective approach to semi-supervised learning. The key idea is to let the learner itself iteratively generate "pseudo-supervision" for unlabeled instances based on its current hypothesis. In combination with consistency regularization, pseudo-labeling has shown promising performance in various domains, for example in computer vision. To account for the hypothetical nature of the pseudo-labels, these are commonly provided in the form of probability distributions. Still, one may argue that even a probability distribution represents an excessive level of informedness, as it suggests that the learner precisely knows the ground-truth conditional probabilities. In our approach, we therefore allow the learner to label instances in the form of credal sets, that is, sets of (candidate) probability distributions. Thanks to this increased expressiveness, the learner is able to represent uncertainty and a lack of knowledge in a more flexible and more faithful manner. To learn from weakly labeled data of that kind, we leverage methods that have recently been proposed in the realm of so-called superset learning. In an exhaustive empirical evaluation, we compare our methodology to state-of-the-art self-supervision approaches, showing competitive to superior performance especially in low-label scenarios incorporating a high degree of uncertainty.

Quantifying the Impact of Location Data for Real Estate Appraisal – A GIS-based Deep Learning Approach - Kucklick, Jan-Peter; Müller, Jennifer; Beverungen, Daniel; Müller, Oliver (European Conference on Information Systems)

A new Device for Determination of Forming-Limit-Curves under Hot-Forming Conditions - Triebus, Marcel; Gierse, Jan; Marten, Thorsten; Tröster, Thomas (IOP Conference Series: Materials Science and Engineering)

COVID-19 reporting and willingness to pay for leisure activities - Warkulat, Sonja; Krull, Sebastian; Ortmann, Regina; Klocke, Nina; Pelster, Matthias (Covid Economics)
The containment of COVID-19 critically hinges on individuals’ behavior. We investigate how individuals react to variations in COVID-19 reporting. Using a survey, we elicit individuals' perceived infection risk given various COVID-19 metrics (e.g., confirmed cases, reproduction rate, or case-fatality ratio). We proxy individuals' risk perception with their willingness to pay for the participation in everyday life and amusements events. We find that participants react to different COVID-19 metrics with varying sensitivity. We observe a saturation of sensitivity for several measures at critical limits used in the political discussion, making our results highly relevant for policy makers in their efforts to direct individuals to adhere to hygienic etiquette and social distancing guidelines.
Keywords: COVID-19 reporting; willingness to pay; willingness to accept

Self-Learning Multi-Objective Service Coordination Using Deep Reinforcement Learning - Schneider, Stefan Balthasar; Khalili, Ramin; Manzoor, Adnan; Qarawlus, Haydar; Schellenberg, Rafael; Karl, Holger; Hecker, Artur (Transactions on Network and Service Management)
Modern services consist of interconnected components,e.g., microservices in a service mesh or machine learning functions in a pipeline. These services can scale and run across multiple network nodes on demand. To process incoming traffic, service components have to be instantiated and traffic assigned to these instances, taking capacities, changing demands, and Quality of Service (QoS) requirements into account. This challenge is usually solved with custom approaches designed by experts. While this typically works well for the considered scenario, the models often rely on unrealistic assumptions or on knowledge that is not available in practice (e.g., a priori knowledge). We propose DeepCoord, a novel deep reinforcement learning approach that learns how to best coordinate services and is geared towards realistic assumptions. It interacts with the network and relies on available, possibly delayed monitoring information. Rather than defining a complex model or an algorithm on how to achieve an objective, our model-free approach adapts to various objectives and traffic patterns. An agent is trained offline without expert knowledge and then applied online with minimal overhead. Compared to a state-of-the-art heuristic, DeepCoord significantly improves flow throughput (up to 76%) and overall network utility (more than 2x) on realworld network topologies and traffic traces. It also supports optimizing multiple, possibly competing objectives, learns to respect QoS requirements, generalizes to scenarios with unseen, stochastic traffic, and scales to large real-world networks. For reproducibility and reuse, our code is publicly available.
Keywords: network management; service management; coordination; reinforcement learning; self-learning; self-adaptation; multi-objective

Zum Zusammenhang von Berufsethos und der Berufswahlmotivation angehender Wirtschaftspädagog*innen - Goller, Michael; Ziegler, Simone (bwp@ Spezial)
Sowohl Berufsethos als auch Berufswahlmotivation tragen zu relevanten lern-, leistungs- und laufbahnbedingenden Prozessen eines Individuums bei und prägen dessen Lebensverlauf wesentlich. Während die Berufswahlmotivation bereits verstärkt im wirtschaftspädagogischen Kontext untersucht wurde, existieren zum Berufsethos von Wirtschaftspädagog*innen nur vereinzelt empirische Studien. So ist beispielsweise wenig darüber bekannt, wie das Berufsethos von Wirtschaftspädagog*innen in der Ausbildungsphase ausgeprägt ist. Auch die Erforschung des Zusammenhangs zwischen den Konstrukten des Berufsethos und der Berufswahlmotivation blieb bisher unbeachtet. In diesem Beitrag wird entsprechend dieses Forschungsdesiderats untersucht, wie das anfänglich ausgebildete Berufsethos von Wirtschaftspädagogikstudierenden in der universitären Ausbildung ausgeprägt ist, ob sich die Ausprägung nach dem angegebenen Berufswunsch der Studierenden unterscheidet und inwiefern das anfänglich ausgeprägte Berufsethos mit der Berufswahlmotivation von Studierenden zusammenhängt. Dafür wurden im Wintersemester 2019/20 an zwölf deutschen Universitäten insgesamt 879 Wirtschaftspädagogikstudierende schriftlich befragt. Die Ergebnisse zeigen, dass das anfängliche Berufsethos der Befragten bereits in der universitären Ausbildungsphase relativ stark ausgeprägt ist. Weiterhin ist zu erkennen, dass das Berufsethos bei angehenden Wirtschaftspädagog*innen, die den Berufswunsch Lehrkraft haben, ausgeprägter ist als bei Wirtschaftspädagogikstudierenden, die eine Tätigkeit außerhalb des Schuldienstes anstreben bzw. noch unentschlossen sind. Letztlich kann aufgezeigt werden, dass grundsätzlich positive Zusammenhänge zwischen dem anfänglich ausgeprägten Berufsethos und der Berufswahlmotivation von angehenden Wirtschaftspädagog*innen bestehen.
Keywords: Berufsethos; Berufswahlmotivation; Wirtschaftspädagogik; Studierende

Spectral Properties of Effective Dynamics from Conditional Expectations - Nüske, Feliks; Koltai, Péter; Boninsegna, Lorenzo; Clementi, Cecilia (Entropy)
The reduction of high-dimensional systems to effective models on a smaller set of variables is an essential task in many areas of science. For stochastic dynamics governed by diffusion processes, a general procedure to find effective equations is the conditioning approach. In this paper, we are interested in the spectrum of the generator of the resulting effective dynamics, and how it compares to the spectrum of the full generator. We prove a new relative error bound in terms of the eigenfunction approximation error for reversible systems. We also present numerical examples indicating that, if Kramers–Moyal (KM) type approximations are used to compute the spectrum of the reduced generator, it seems largely insensitive to the time window used for the KM estimators. We analyze the implications of these observations for systems driven by underdamped Langevin dynamics, and show how meaningful effective dynamics can be defined in this setting.

Resonant evanescent excitation of guided waves with high-order optical angular momentum - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Journal of the Optical Society of America B)
Gaussian-beam-like bundles of semi-guided waves propagating in a dielectric slab can excite modes with high-order optical angular momentum supported by a circular fiber. We consider a multimode step-index fiber with a high-index coating, where the waves in the slab are evanescently coupled to the modes of the fiber. Conditions for effective resonant interaction are identified. Based on a hybrid analytical–numerical coupled mode model, our simulations predict that substantial fractions of the input power can be focused into waves with specific orbital angular momentum, of excellent purity, with a clear distinction between degenerate modes with opposite vorticity.
Keywords: tet_topic_waveguides

An efficient descent method for locally Lipschitz multiobjective optimization problems - Gebken, Bennet; Peitz, Sebastian (Journal of Optimization Theory and Applications)
In this article, we present an efficient descent method for locally Lipschitz continuous multiobjective optimization problems (MOPs). The method is realized by combining a theoretical result regarding the computation of descent directions for nonsmooth MOPs with a practical method to approximate the subdifferentials of the objective functions. We show convergence to points which satisfy a necessary condition for Pareto optimality. Using a set of test problems, we compare our method to the multiobjective proximal bundle method by M\"akel\"a. The results indicate that our method is competitive while being easier to implement. While the number of objective function evaluations is larger, the overall number of subgradient evaluations is lower. Finally, we show that our method can be combined with a subdivision algorithm to compute entire Pareto sets of nonsmooth MOPs.

Inverse multiobjective optimization: Inferring decision criteria from data - Gebken, Bennet; Peitz, Sebastian (Journal of Global Optimization)
It is a challenging task to identify the objectives on which a certain decision was based, in particular if several, potentially conflicting criteria are equally important and a continuous set of optimal compromise decisions exists. This task can be understood as the inverse problem of multiobjective optimization, where the goal is to find the objective function vector of a given Pareto set. To this end, we present a method to construct the objective function vector of an unconstrained multiobjective optimization problem (MOP) such that the Pareto critical set contains a given set of data points with prescribed KKT multipliers. If such an MOP can not be found, then the method instead produces an MOP whose Pareto critical set is at least close to the data points. The key idea is to consider the objective function vector in the multiobjective KKT conditions as variable and then search for the objectives that minimize the Euclidean norm of the resulting system of equations. By expressing the objectives in a finite-dimensional basis, we transform this problem into a homogeneous, linear system of equations that can be solved efficiently. Potential applications of this approach include the identification of objectives (both from clean and noisy data) and the construction of surrogate models for expensive MOPs.

Observing 0D subwavelength-localized modes at ~100 THz protected by weak topology - Lu, Jinlong; Wirth, Konstantin G.; Gao, Wenlong; Heßler, Andreas; Sain, Basudeb; Taubner, Thomas; Zentgraf, Thomas (Science Advances)
Topological photonic crystals (TPhCs) provide robust manipulation of light with built-in immunity to fabrication tolerances and disorder. Recently, it was shown that TPhCs based on weak topology with a dislocation inherit this robustness and further host topologically protected lower-dimensional localized modes. However, TPhCs with weak topology at optical frequencies have not been demonstrated so far. Here, we use scattering-type scanning near-field optical microscopy to verify mid-bandgap zero-dimensional light localization close to 100 THz in a TPhC with nontrivial Zak phase and an edge dislocation. We show that because of the weak topology, differently extended dislocation centers induce similarly strong light localization. The experimental results are supported by full-field simulations. Along with the underlying fundamental physics, our results lay a foundation for the application of TPhCs based on weak topology in active topological nanophotonics, and nonlinear and quantum optic integrated devices because of their strong and robust light localization.

Lossless, Persisted Summarization of Static Callgraph, Points-To and Data-Flow Analysis - Schubert, Philipp; Hermann, Ben; Bodden, Eric (European Conference on Object-Oriented Programming (ECOOP))
Static analysis is used to automatically detect bugs and security breaches, and aids compileroptimization. Whole-program analysis (WPA) can yield high precision, however causes long analysistimes and thus does not match common software-development workflows, making it often impracticalto use for large, real-world applications.This paper thus presents the design and implementation ofModAlyzer, a novel static-analysisapproach that aims at accelerating whole-program analysis by making the analysis modular andcompositional. It shows how to computelossless, persisted summaries for callgraph, points-to anddata-flow information, and it reports under which circumstances this function-level compositionalanalysis outperforms WPA.We implementedModAlyzeras an extension to LLVM and PhASAR, and applied it to 12 real-world C and C++ applications. At analysis time,ModAlyzermodularly and losslessly summarizesthe analysis effect of the library code those applications share, hence avoiding its repeated re-analysis.The experimental results show that the reuse of these summaries can save, on average, 72% ofanalysis time over WPA. Moreover, because it is lossless, the module-wise analysis fully retainsprecision and recall. Surprisingly, as our results show, it sometimes even yields precision superior toWPA. The initial summary generation, on average, takes about 3.67 times as long as WPA.

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Automated Machine Learning for Multi-Label Classification - Wever, Marcel Dominik

The influence of manufacturing processes and optical measurement methods on the damage behavior of HX340LAD micro-alloyed steels - Otroshi, Mortaza; Meschut, Gerson; Nesakumar, Aathavan (Journal of Manufacturing Engineering)
This study deals with the damage behavior of metallic materials by the application of different manufacturing processes and using different optical measurement methods to identify the crack initiation in the damage specimen. The study is intended to highlight the importance of considering manufacturing processes and optical measurement methods in a numerical simulation when analyzing the damage behavior of metallic materials. To describe the damage behavior of the material in the process chain simulations, it is important to calibrate the parameters of damage model more accurately. These parameters are determined using experimental investigation of desired damage specimens. In this regard, a selected damage specimen manufactured by different cutting processes is first experimentally and then numerically investigated. It is shown that the manufacturing process and the optical measurement methods influence the stress state analyzed in the numerical simulation.
Keywords: Damage behaviour; Stress triaxiality; Manufacturing process and Optical measurement

Towards a Decision Support System for Cross-Sectoral Energy Distribution Network Planning - Kirchhoff, Jonas; Burmeister, Sascha Christian; Weskamp, Christoph; Engels, Gregor (Energy Informatics and Electro Mobility ICT)
Requirements for energy distribution networks are changing fast due to the growing share of renewable energy, increasing electrification, and novel consumer and asset technologies. Since uncertainties about future developments increase planning difficulty, flexibility potentials such as synergies between the electricity, gas, heat, and transport sector often remain unused. In this paper, we therefore present a novel module-based concept for a decision support system that helps distribution network planners to identify cross-sectoral synergies and to select optimal network assets such as transformers, cables, pipes, energy storage systems or energy conversion technology. The concept enables long-term transformation plans and supports distribution network planners in designing reliable, sustainable and cost-efficient distribution networks for future demands.

Classifying the Ideational Impact of Information Systems Review Articles: A Content-Enriched Deep Learning Approach - Prester, Julian; Wagner, Gerit; Schryen, Guido; Hassan, Nik Rushdi (Decision Support Systems)
Ideational impact refers to the uptake of a paper's ideas and concepts by subsequent research. It is defined in stark contrast to total citation impact, a measure predominantly used in research evaluation that assumes that all citations are equal. Understanding ideational impact is critical for evaluating research impact and understanding how scientific disciplines build a cumulative tradition. Research has only recently developed automated citation classification techniques to distinguish between different types of citations and generally does not emphasize the conceptual content of the citations and its ideational impact. To address this problem, we develop Deep Content-enriched Ideational Impact Classification (Deep-CENIC) as the first automated approach for ideational impact classification to support researchers' literature search practices. We evaluate Deep-CENIC on 1,256 papers citing 24 information systems review articles from the IT business value domain. We show that Deep-CENIC significantly outperforms state-of-the-art benchmark models. We contribute to information systems research by operationalizing the concept of ideational impact, designing a recommender system for academic papers based on deep learning techniques, and empirically exploring the ideational impact of the IT business value domain.
Keywords: Ideational impact; citation classification; academic recommender systems; natural language processing; deep learning; cumulative tradition